Analisis Kemampuan Berpikir Tingkat Tinggi Mahasiswa dalam Mata Kuliah Statistik - Hugo Theo Kurniason (Departement of Mathematics Education, 2022)
Thinking skills is one of the factors that determine the success of learning statistics. Higher order thinking skills are part of thinking skills, so that higher order thinking skills also determine the success of learning statistics. This study aims to describe the higher order thinking skills of Sekolah Tinggi Agama Katolik Negeri Pontianak students in statistics. This study used qualitative methods. The results of this study indicate that the higher order thinking skills of Sekolah Tinggi Agama Katolik Negeri Pontianak students are in the low category. When viewed for each indicator, the ability to analyze, evaluate, and create is in the low category.